Musical style of reception – a musical interpretant – musical form in literature - Aleksandra Reimann (Przestrzenie Teorii)
The paper is concerned with reception strategies where interdisciplinary competencies are connected to musical expectations towards a text, which – i.a. because of metatextual suggestions – needs a musical explanation – “musical supplement”. The objective of the article is the musical and literary dialog, which belongs to intermediality (definition by W. Wolf), and intertextuality in the large sense as well. Although the penetration of musical and literary correspondence does not threaten “scientist hysteria”, it also does not promise fruitful strategies and satisfactory conclusions. The paper includes terminological proposals which are an attempt at universal, semiotic transposition into musical and literary borderland, which in the practice of interpretation has too eclectic, and mostly one-time solutions.